2013
DOI: 10.1002/tcr.201300001
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Polymer‐Supported Nanometal Catalysts in Water

Abstract: Two types of polymer-supported nanometal catalysts with high catalytic activity and recyclability in water have been developed. One catalyst was composed of linear polystyrene-stabilized metal nanoparticles (PS-MtNPs). A palladium catalyst (PS-PdONPs) was prepared in water by the thermal decomposition of Pd(OAc)2 in the presence of polystyrene. The degree of immobilization of Pd, but not the size of the Pd nanoparticles, was dependent on the molecular weight and cross-linking of the polystyrene. The PS-PdONPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 134 publications
0
13
0
Order By: Relevance
“…Silica is a very versatile material that can be prepared with good control of particle size and morphology. For example, silica nanospheres can be synthesised by means of microemulsions [31, 51, 52] or by modified synthesis of Stöber sol–gels [72] …”
Section: Catalysts Supported On Functionalised Silicamentioning
confidence: 99%
See 1 more Smart Citation
“…Silica is a very versatile material that can be prepared with good control of particle size and morphology. For example, silica nanospheres can be synthesised by means of microemulsions [31, 51, 52] or by modified synthesis of Stöber sol–gels [72] …”
Section: Catalysts Supported On Functionalised Silicamentioning
confidence: 99%
“…Approaches that use photolytic degradation by sunlight [16] and biological pathways, [17] as well as their hydrolysis by biomimetic compounds, have been employed to solve the problem of the natural persistence of such compounds [18–30] . The use of biomimetic compounds offers a number of advantages, including the possibility to immobilise these compounds on the surface of insoluble solid matrices for easier handling and reuse [31] …”
Section: Introductionmentioning
confidence: 99%
“…We have also found that, in BmimBF 4 , methylenedihydrobenzofuranols 2 can be readily converted into 2-hydroxymethylbenzofurans 3 or 2-methoxymethylbenzofurans 4 by acid-catalyzed allylic isomerization or allylic nucleophilic substitution in a one-pot fashion. The recyclability of metal catalysts has acquired an increasing importance in the modern organic synthesis, as testified by recent publications in this field [32,33,34,35,36,37,38,39,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…19,20 A shift toward palladium nanoparticles has been apparent in the past decade because they offer the benefits of heterogeneous catalysis. [21][22][23][24] Although their role in catalysis is not well understood, metal nanoparticles provide advantages specific to both heterogeneous and homogeneous catalysts and because of that are sometimes called "semi-heterogeneous" catalysts. 21 These advantages relate to the fact that small clusters of metals in low oxidation states are stabilized in solution, and include recoverability and reusability as well as high activity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…21,22,30,31 In general, a reducing agent is required for palladium nanoparticle formation. [21][22] Polyaniline (PANI), [32][33][34][35] however, provides both stabilization and reducing properties. PANI has been used for various applications due to its electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%